Systematic review and meta-analysis on prevalence, pattern, and factors associated with ocular protection practices among welders in sub-Saharan Africa - Atalay, Yibeltal Assefa; Gebeyehu, Natnael Atnafu; Gelaw, Kelemu Abebe (Frontiers in Public Health, 2024)
Background Due to hazardous working conditions, welders are more likely to be exposed to mild to severe eye issues during the welding process. Globally, this issue is a major contributor to vision loss and blindness. One of the most frequent causes of unilateral blindness in the globe is ocular injury. Objective This review aimed to assess the pooled prevalence of ocular protection practice and associated factors among welders in sub-Saharan Africa. Methods Databases including PubMed, Scopus, web of Science, Google Scholar, and the African Journals Online were systematically searched for relevant literature. The statistical analysis was performed using STATA data analysis software version 14, while Microsoft Excel was used for data abstraction. We checked publication bias using a funnel plot and Egger and Begg regression tests. A p-value < 0.05 was considered significant, suggesting the presence of presence publication bias. The I2 statistics were used to assess heterogeneity between studies. The study's overall effect was evaluated using the random effects model. Results From retrieved 2,326 original studies, 17 studies were included in the final pooled prevalence analysis. The overall prevalence of ocular protection practice among small-scale welders in sub-Saharan Africa was 53.71% (95% CI: 42.54, 64.88). Having pre and in-service training [AOR: 4.97, 95% CI: (2.64, 9.36)], having work experience as a welder [AOR: 4.94, 95% CI: (3.24, 7.54)], and having a history of ocular injury [AOR: 2.99, 95% CI: (1.58, 5.66)] were significantly associated with the ocular protection practices. Conclusions In sub-Saharan African countries, the ocular protection practices among small-scale welders were low. Furthermore, the current meta-analysis found ocular protection practice to be significantly associated with on-the-job training, work experience of welders, and a history of ocular injury in the past year of small-scale welders in sub-Saharan Africa. This review will serve as baseline data for further studies to generate inputs for eye care providers and policymakers to improve good practice levels about ocular protection. Policies should be put in place to ensure all welders use proper personal–protective equipment, and receive regular health training.